Análise de fatores determinantes no processo de internacionalização de empresas de pequeno porte - Lina Siqueira Kroeber Volpini de Carvalho (2005)
The process of economic opening in Brazil occurred simultaneously with the increase of the globalization movement and created a more competitive entrepreneurial cenario in Brazil as well as new internationalization opportunities for brazilian companies. However these opportunities have not become a reality to most of the small businesses. This study attempted to understand better the path these enterprises choose to initiate the export activity through the identification of determining factors and internal resources in the export process of small imitation jewelry companies in the state of Minas Gerais. The results indicate that the existence of some patterns of determining factors can be considered mostly associated with the manager export attitude and international orientation, his level of motivation towards the internationalization of his business, a solid productive structure and originality of the companys product although, the incentives and opportunities found in the external environment represent a fundamental factor on the export decision of this companies as well as the factors associated with its size such as flexibility and readiness for market reply. The importance of internal resources is considered by the owners in the export decision process but there is no formal export readiness investigation nor an analysis of the impact those factors will have on the export behavior of the company in the long term period.